Enzyme Catalysis To Power Micro/Nanomachines - Ma, Xing (ACS Nano, 2016)
[Image: see text] Enzymes play a crucial role in many biological processes which require harnessing and converting free chemical energy into kinetic forces in order to accomplish tasks. Enzymes are considered to be molecular machines, not only because of their capability of energy conversion in biological systems but also because enzymatic catalysis can result in enhanced diffusion of enzymes at a molecular level. Enlightened by nature’s design of biological machinery, researchers have investigated various types of synthetic micro/nanomachines by using enzymatic reactions to achieve self-propulsion of micro/nanoarchitectures. Yet, the mechanism of motion is still under debate in current literature. Versatile proof-of-concept applications of these enzyme-powered micro/nanodevices have been recently demonstrated. In this review, we focus on discussing enzymes not only as stochastic swimmers but also as nanoengines to power self-propelled synthetic motors. We present an overview on different enzyme-powered micro/nanomachines, the current debate on their motion mechanism, methods to provide motion and speed control, and an outlook of the future potentials of this multidisciplinary field.